Effect of ultraviolet irradiation on fish pathogens Vibrio spp. and aeromonas hydrophila. - Garcia, Janice S.
The application of lethal doses of ultraviolet (UV) radiation for microbial control in modern aquaculture systems has been a widespread practice. As a surface-active disinfectant, the presence of water and other interfering particles renders it sublethal to bacterial fish pathogens naturally inhabiting hatchery water systems. Information on the sublethal effects of UV on the antimicrobial responses, and on the virulence of fish pathogens can aid aquaculturists and policy makers on UV limitations and use. This study aimed (1) to determine the effect of UV sublethal dose on colony growths of bacterial fish pathogens Vibrio spp. and Aeromonas hydrophila based on their antimicrobial susceptibility and biochemical characteristics; and (2) to determine the effect of UV sublethal dose treatment of the said pathogens on their pathogenicity to Penaeus monodon postlarvae., The study was conducted using five bacterial isolates Vibrio anguillarium V. harveyi, V parachaemolyticus, of the UV sublethal dose for five isolates. Antimicrobial susceptibility and biochemical tests using standard procedures were performed before and after UV treatment. Virulence screening of UV treated isolates was carried out on healthy P. monodon postlarvae (PL20) at an inoculum of 10FD CFU/ml. Data on mortality after 6,12,18, and 24 hours were analyzed using the two-way analysis of variance(ANOVA) with interaction. The UV lethal dose of the isolates was at 15 minutes except for Vibrio sp. from seaweed which was at 19-20 minutes using light and dark incubation. Thd five isolates showed varying ranges of UV sublethal dose under light incubation. Significant changes in response to chloramphenicol, penicillin, and isoniazid were observed in most of the isolates after UV treatment. Biochemical tests involving indole and hydrogen sulfide production, citrate utilization, triple sugar iron agar (TSIA), and motility also produced notable changes in the response of the isolates. Ultraviolet treatment of the isolates show significant differences in mortality for the first 18 hours after inoculation. All isolates produced 100 mortality of shrimp postlarvae after 24 hours. The UV sublethal dose possibly affects the bacterial cell wall, the ribosomal 50S subunit, and the NAD metabolism as changes in response to penicillin, chloramphenicol, and isoniazid were observed. UV treatment probably produces no effect on DNA material, the cell membrane, and the 30S subunit of the ribosome. Biochemical tests involving metabolic pathways and products may also be affected by UV sublethal dose. The decrease in the virulence of the isolates to P. monodon postlarvae after UV treatment may be attributed to the inhibitory effect of the sublethal dose on pathogens.